2013
DOI: 10.1007/s12161-013-9776-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Antioxidative Activity of Flavonoids Using HPLC–ED and Photometric Assays

Abstract: The present investigation reports on the application of a new antioxidant activity assay for the examination of flavonoids. It has been shown that the high-performance liquid chromatography with electrochemical detection (HPLC-ED) measurements allow to obtain additional information about the antioxidative properties of pure compounds by measuring their half-wave potential, the chromatographic peak height, and the product of the peak height and exponent of potential. In comparison to the classical electrochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In addition, one of the quercetin derivatives has proven to have a protective effect on the intact β-cells of the islets of Langerhans by inhibiting lipid peroxidation, as well as its ability to scavenge free radicals from STZ-induced oxidative stress in STZ-induced diabetic rats [ 20 ]. Although no research has been conducted regarding the proficiency of 6-hydroxyflavanone on directly reducing the blood glucose level, there are some studies that have demonstrated the electron donating ability of 6-hydroxyflavanone to scavenge free radicals induced by 2,2-diphenyl-1-picrylhydrazyl in in vitro antioxidant study [ 21 , 59 ]. Besides that, kaempferol, another flavonoid-type compound that was identified and quantified, also reportedly shows hypoglycemic effect by lowering the levels of glycoprotein in the liver and increment of insulin production, as well as enhancement of glucose utilization in STZ-induced rats [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one of the quercetin derivatives has proven to have a protective effect on the intact β-cells of the islets of Langerhans by inhibiting lipid peroxidation, as well as its ability to scavenge free radicals from STZ-induced oxidative stress in STZ-induced diabetic rats [ 20 ]. Although no research has been conducted regarding the proficiency of 6-hydroxyflavanone on directly reducing the blood glucose level, there are some studies that have demonstrated the electron donating ability of 6-hydroxyflavanone to scavenge free radicals induced by 2,2-diphenyl-1-picrylhydrazyl in in vitro antioxidant study [ 21 , 59 ]. Besides that, kaempferol, another flavonoid-type compound that was identified and quantified, also reportedly shows hypoglycemic effect by lowering the levels of glycoprotein in the liver and increment of insulin production, as well as enhancement of glucose utilization in STZ-induced rats [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Compared with UV and DAD, ECD can identify changes in the electrical signals of substances and selectively detect compounds with oxidizing or reducing abilities [24][25][26]. Indeed, electrochemistry is an effective means for evaluating the antioxidant activity of a species, wherein it has been documented that there is a significant correlation between the DPPH scavenging activity and the peak height or the first half-wave potential [27,28]. Phenolic acids and flavonoids tend to exhibit superior response values by HPLC-electrochemical detection (HPLC-ECD) than compounds that do not bear phenolic hydroxyl groups [26,29].…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids are phenolic compounds with a chemical structure of C 6 -C 3 -C 6 . Flavonoids have the conjugated bonds, there is a single bonded (C-C) and double bonded (C = C) carbon atoms intermittent [16].…”
Section: Introductionmentioning
confidence: 99%